Clinical manifestations, disease activity and disease burden of radiographic versus non-radiographic axial spondyloarthritis over 5 years of follow-up in the DESIR cohort. Issue 2 (29th November 2019) - López-Medina, Clementina; Molto, Anna; Claudepierre, Pascal; Dougados, Maxime
Abstract : Objectives: To compare the clinical manifestations, disease activity and disease burden between patients with radiographic (r-axSpA) and non-radiographic axial spondyloarthritis (nr-axSpA) over a 5-year follow-up period in the Devenir des Spondylarthropathies Indifferénciées Récentes (DESIR) cohort. Methods: Patients from the DESIR cohort who had X-ray images of the sacroiliac joints available at baseline and did not leave the study during the 5-year follow-up period because of a diagnosis other than axSpA were included. A unilateral rating of 'obvious sacroiliitis' by the local reader was considered sufficient for classification as r-axSpA. The incidence of first episodes of peripheral and extra-rheumatic manifestations was compared between the two groups using the incidence rate ratio and Cox regressions adjusted for sex, age and tumour necrosis factor blocker (TNFb) intake. Mean values of patient-reported outcomes (PROs) and days of sick leave over 5 years of follow-up were compared using mixed models adjusted for sex, age, TNFb intake and baseline values. Results: In total, 669 patients were included, of whom 185 (27.7%) and 484 (72.3%) were classified as r-axSpA and nr-axSpA, respectively. At baseline, the r-axSpA patients showed a significantly higher prevalence of males. After adjusting for age, sex and TNFb intake, Cox regressions for peripheral and extra-rheumatic manifestations did not show any significant differences between groups. Mixed models also showed similar mean levels in PROs and days of sick leave between groups over time. Conclusion: The incidence of peripheral and extra-rheumatic manifestations as well as the disease burden over time remained similar between r-axSpA and nr-axSpA groups after adjusting for intermediate variables. Trial registration number: NCT01648907